Clinical impact of endoscopic ultrasonography for small rectal neuroendocrine tumors - Jae Hyun Kim; Won Moon; Seun Ja Park; Moo In Park; Sung Eun Kim; Ki Hwan Ku; Gyu Won Lee; Youn Jung Choi (Turkish Journal of Gastroenterology, 2019)
Background/Aims: Endoscopic ultrasonography (EUS) is helpful for evaluating the depth of tumor invasion and lymph node metastasis of rectal neuroendocrine tumors (NETs). The aim of this study was to clarify the clinical impact of EUS for rectal NETs less than 10 mm in diameter. Materials and Methods: : A total of 76 rectal NETs treated at our hospital between June 2006 and March 2013 were reviewed retrospectively. All lesions were analyzed with EUS to evaluate the depth of tumor invasion. The lesions were resected by endoscopic submucosal resection with band ligation (ESMR-L) or endoscopic submucosal dissection (ESD) and examined histologically. Results: Endoscopic ultrasonography findings showed that all lesions were confined to the submucosa and revealed no adjacent lymph node metastasis. Seventy-five of the 76 lesions were completely resected by ESMR-L. One lesion was resected by ESD and the resected deep margin of the lesion was histologically positive. Only one lesion exhibited lymphatic invasion. Conclusion: EUS may not be essential for diagnosis and treatment planning for rectal NETs less than 10 mm in size.